Thidiazuron induces high frequency direct somatic embryogenesis growth from cotyledon culture of eurycoma longifolia - Zawawi Dhiya Dalila,; Ja’afar Hafsah,; Zainuddin Rokiah,; Kari Rodziah,; Mohd Noor Madihah, (Universiti Kebangsaan Malaysia, 2015)
Eurycoma longifolia is one of the well-known herbal plants in Southeast Asian region due to its remarkable properties, especially the root part that can be used as aphrodisiac, anti-cancer, anti-malaria and anti-ulcer agent. Uncontrolled harvesting of this plant has reduced its population. Thus, an efficient protocol involving the induction of direct somatic embryogenesis from cotyledon culture of E. longifolia has been developed. 15% explants forming embryos were achieved on Modified Murashige and Skoog’s (MMS) medium supplemented with 0.1 mg/L zeatin plus 0.2 mg/L indole-3-butyric acid (IBA). However, the addition of 0.12 mg/L thidiazuron (TDZ) has increased the percentage up to 22.0%. The maturation phase occurred in the same medium, thus decreased the frequency of subculture and the genetic instability of the embryos. Secondary somatic embryogenesis growth of 20%, which was the highest percentage of growth, was achieved from the primary embryos that were cultured in the MMS medium with the treatment of 2.0 mg/L IBA plus 0.075 mg/L TDZ. The results indicated that the direct somatic embryogenesis obtained can be further used to develop a protocol for plantlet regeneration of E. longifolia.